Production of Planetary Mechanism Model Prototype using Additive Method of Rapid Prototyping - Sedlak, Josef; Kudlacova, Barbora; Zemcik, Oskar; Jaros, Ales; Slany, Martin (Manufacturing Technology Journal, 2017)
An article deals with a production of a planetary mechanism model prototype using an additive method of Rapid Prototyping (RP) by a 3D printer called uPrint. The first part of the article contains a theoretical analysis of a main principle and kinematics parameters of the planetary mechanism model. The second part begins with an experimental analysis of a planetary assembly calculation and continues with a description of a production process of all individual mechanism parts and description of the final completing of the planetary mechanism prototype. The final part deals with a characterization of ABS styrene polymers generally used for production printed by uPrint device.
Keywords: Additive Method; Rapid Prototyping; Fused Deposition Modelling; uPrint; Planetary Mechanism; ABS Styrene Polymer